ROS-mediated apoptosis in colon cancer cells induced by sulfated polysaccharides from Gracilaria corticata - Zeynab Falihzadeh; Laleh Roomiani (PLoS ONE, 2026)
Background Sulfated polysaccharides (SPs) from red algae have attracted considerable interest due to their antioxidant and anticancer properties. Gracilaria corticata is a rich source of sulfated polysaccharides with notable antioxidant and anticancer potential. Objectives This study aimed to optimize the extraction process of SPs from G. corticata, determine their chemical and structural features, and evaluate their antioxidant and anticancer activities. Materials and methods The SPs were extracted from G. corticata using ultrasound-assisted extraction. The chemical composition, molecular weight (230 kDa), and structure of the extracted SPs were characterized using standard biochemical assays and nuclear magnetic resonance (NMR) spectroscopy. Antioxidant capacity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assays. Cytotoxicity was assessed against HT-29 colon cancer cells and normal CCD-841 cells via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis induction was further examined through Annexin V-FITC/PI staining and gene expression analysis of apoptosis-related markers. Results Ultrasound-assisted extraction was optimized at 12 min, 800 W power, and a solvent-to-biomass ratio of 30 mL/g, yielding 34.8% SPs. The SPs contained 84.4% carbohydrates, 8.7% sulfate, and 2.55% protein, with galactose identified as the predominant sugar. Molecular weight was determined to be 230 kDa. Antioxidant assays demonstrated dose-dependent activity, reaching 81.92% (DPPH) and 86.34% (ABTS) radical scavenging. SPs inhibited HT-29 cell viability with an IC₅₀ of 171 μg/mL and a selectivity index (SI) of 3.48. Apoptosis was induced via increased intracellular reactive oxygen species (ROS) and altered expression of key genes, including upregulation of Bax , P53 , and Caspase 3 , and downregulation of BCL2 . Conclusions SPs extracted from G. corticata, show strong antioxidant and selective anticancer activity through ROS-mediated apoptosis. These findings support their potential use as natural therapeutic agents in pharmaceutical development.